A diminutive pelecinid wasp from the Eocene Kishenehn Formation of northwestern Montana (Hymenoptera: Pelecinidae) - Greenwalt, Dale; Engel, Michael S. (Novitates Paleoentomologicae, 2014)
A new genus and species of pelecinid wasp (Proctotrupoidea: Pelecinidae) is described and figured from a single male preserved in oil shale from the middle Eocene Kishenehn Formation of northwestern Montana.  Phasmatopelecinus leonae Greenwalt & Engel, new genus and species, is distinguished from other Tertiary and Mesozoic pelecinids as well as the Recent genus Pelecinus Latreille.  Despite the fact that there are more than 15 times more fossil than living species in the family, P. leonae is only the second Tertiary member of the family discovered to date.